2018
DOI: 10.1142/s1363919618500184
|View full text |Cite
|
Sign up to set email alerts
|

ORGANISATIONAL FACTORS, ANTICIPATED RENTS AND COMMERCIALISATION IN SMEs

Abstract: The study investigates the relationship between organisational factors and the anticipated returns to the commercialisation of an innovation within small to medium enterprises (SMEs). Using a large multi-country sample, the analysis involved a structural equation model of seven organisational factors associated with the management of innovation, and their relationship with the anticipated volume of sales, profitability and lifecycle of the innovation. Significant relationships were found between the possession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Dobni (2008) and Miron et al (2004) define organizational culture as a framework of shared values and beliefs for employees at all levels of the organization that are reflected in its characteristics. Do et al (2018), Pedersen et al (2018) and Tellis (2012) also argue that organizational culture is one of the principal factors that affect innovation in organizations despite the difficulty in measuring and controlling it. Tellis (2012) and Tellis et al (2009) define organizational culture as a basic set of approaches and practices shared by members of the organization and claim that a culture that fosters innovation will assist the business to stay ahead in the long term.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dobni (2008) and Miron et al (2004) define organizational culture as a framework of shared values and beliefs for employees at all levels of the organization that are reflected in its characteristics. Do et al (2018), Pedersen et al (2018) and Tellis (2012) also argue that organizational culture is one of the principal factors that affect innovation in organizations despite the difficulty in measuring and controlling it. Tellis (2012) and Tellis et al (2009) define organizational culture as a basic set of approaches and practices shared by members of the organization and claim that a culture that fosters innovation will assist the business to stay ahead in the long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The decision to focus on cultural processes was based on the contention made in many studies that organizational culture is considered as a key innovation resource and is conducive to a business's growth and performance (Ali and Park, 2016; Rohlfer and Zhang, 2016; Tian et al , 2018). The current study focuses on examining these processes in small businesses, which may fundamentally differ from those implemented in larger businesses, on which most of the previous studies have focused (Centobelli et al , 2017; Do et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As well, this could represent an inefficient allocation of resources, as the final objective has not been successfully achieved. Usually SMEs are resource constrained and frequently lack technical, marketing, financial and managerial resources (Do et al, 2018). However, ‘by virtue of their limited resources, many small businesses are best equipped to pursue niche markets’ (Parnell, 2013: 217).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, a recent systematic literature review notes that surprisingly few studies examined SO and sales management in SME management literature despite its apparent importance to SME survival and growth (Bocconcelli et al, 2018). Research has primarily focused on sales as either a function or an outcome instead of investigating its implications for business approach and performance (see, for example, Do et al, 2018; Miller et al, 2008; Rezaei and Ortt, 2018). Some recent studies have evolved to capture perspectives of the sales phenomenon and its impact on SME performance, such as selling capability (Pratono, 2018), the alignment with sales and marketing (Malshe et al, 2017) and sales as a component of social media orientation (Dutot and Bergeron, 2016).…”
Section: Literature Background and Research Hypothesesmentioning
confidence: 99%
“…Previous studies have shown that organizational culture is an important resource for promoting innovation and contributes greatly to business performance and growth (Ali & Park, 2016;Do et al, 2018;Hoyte, 2019). Organizational culture is defined as a framework of shared values and beliefs for employees at all levels of the organization that are reflected in its characteristics, and organizational culture that encourages innovation includes behaviour that demonstrates an appreciation of creativity, risk-taking, freedom, teamwork, communication, trust and respect (Dobni, 2008;Miron et al, 2004).…”
Section: Processes For Creating An Organizational Culture That Encourages Innovationmentioning
confidence: 99%